The descriptive way to present the character when the poets of Bani Asad - Al-Hayani, Saba Muhammad; Jadwe, Nasra Ahmed (Al-Adab Journal, 2021)
Critics have been interested in the ways of presenting personality and presenting it in narrative work because of its central role in activating the dynamics of the narrative process. The author follows a specific approach in presenting the personality within the work. This approach is usually in one of two ways: Either the author describes the character accurately, or the character appears through the events of the novel itself and the interaction of the personality with them. The description is based on: "the presentation and presentation of objects, objects, facts and events in their spatial rather than temporal and temporal existence rather than their temporal function and their repetition rather than following them". It is the creative person who leaves his imagination to play an important role in drawing his characters, and depends on his understanding of the personality and his perception of the actions that may be issued under certain circumstances. The personality that we find disturbed in any literary work is different from the character we find troubled in life because: "The literary character is made from the imagination of the writer and the link between them and the real character is that it is a technical symbol." If the character is fictional, which is not real, the poet comes to express an issue, but there are some real characters inspired by the poets of reality, so they describe it and draw it to the recipient for the purpose of approximation of the picture, or may resort to the analysis of their actions and actions to bring the image to the recipient. This is what we found in the poets of the sons of Asad. In light of the extrapolations of the poets of Bani Asad, we found more than one way in presenting the personal presentation in the descriptive manner that we will study in this research.